2011
DOI: 10.1016/j.wear.2010.12.001
|View full text |Cite
|
Sign up to set email alerts
|

A note on threshold velocity criteria for modelling the solid particle erosion of WC/Co MMCs

Abstract: The threshold velocity for erosion of a ductile material is considered as the velocity required for initiation of plastic deformation in the substrate. For a brittle material, it defines the velocity required to nucleate a median crack in the elastic/plastic interface beneath the indentation. By invoking models for the solid particle erosion of ductile and brittle materials from the literature, together with a set of criteria based on threshold velocity calculations for erosion of the individual components, va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 21 publications
2
9
0
Order By: Relevance
“…Moreover, the fluctuation in erosive wear peaks can be attributed to the different slurries, angles of attack, particles characteristics and material as composites behave differently than metals (Fig. 4) [21].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the fluctuation in erosive wear peaks can be attributed to the different slurries, angles of attack, particles characteristics and material as composites behave differently than metals (Fig. 4) [21].…”
Section: Discussionmentioning
confidence: 99%
“…The second is acid, concentration with contribution percentage of 5%. The smallest is speed only contribution percentage of 0.4%, such trend could be due to so-called speed threshold effect [34,35,36,37,38,39]. Only when impact speed is higher than threshold value will it cause wear rate transition of the test material [34].…”
Section: Resultsmentioning
confidence: 99%
“…The smallest is speed only contribution percentage of 0.4%, such trend could be due to so-called speed threshold effect [34,35,36,37,38,39]. Only when impact speed is higher than threshold value will it cause wear rate transition of the test material [34]. Although many investigations have indicated that impact velocity is a critical test variable on erosion wear rate [40], in this research the rotational speed of 1200 rpm, i.e., high level, could still not be high enough to reach the threshold velocity.…”
Section: Resultsmentioning
confidence: 99%
“…Erosion maps for ceramics have also been generated using threshold velocity criteria and indicated the importance of particle size and velocity on the erosion rate transitions for these materials. However, Jana and Stack (Jana, 2011) have recently attempted to use such threshold velocity criteria for the ductile and ceramic phases of an metal matrix composite (MMC) to model the erosion behavior of a WC/Co hardmetal. Their erosion model was based on the establishment of critical velocity transitions for the onset of plastic deformation of the ductile matrix material and median crack formation of the brittle reinforcement, with the model predictions showing qualitative agreement with some, but not all, of the trends observed for the solid particle erosion of MMCs in the literature.…”
Section: Threshold Velocitymentioning
confidence: 99%